Matzoh mouse - Wohl, Lauren L.; Keavney, Pamela ([New York] : HarperCollinsPublishers, 1991)
While helping her parents prepare for the Passover seder, nine-year-old Sarah cannot resist nibbling on the chocolate-covered matzoh.
"A Charlotte Zolotow book."
"Ages 5-8"--Jacket.
Booklist
School Library Journal
4.6
K-3
Keywords: Jews -- Fiction; Passover -- Fiction; Passover -- Fiction